Physiological responses of marine organisms to environmental stresses - Dorigan, Janet V.; Harrison, Florence L. (U.S. Dept. of Energy, Office of Energy Research, Office of Health and Environmental Research, Ecological Research Division, 1987)
DOE/ER-0317